Odpowiedzi

Najlepsza Odpowiedź!
2010-02-06T18:14:07+01:00
A = (6, 1)
B = (-2, 5)
C = (-6, -1)

x²+y²-2ax-2by+c=0

A=(6;1)
x²+y²-2ax-2by+c=0
6²+1²-2a*6-2b*1+c=0
36+1-12a-2b+c=0
37-12a-2b+c=0

B=(-2;5)
x²+y²-2ax-2by+c=0
(-2)²+5²-2a*(-2)-2b*5+c=0
4+25+4a-10b+c=0
29+4a-10b+c=0

C=(-6;-1)
x²+y²-2ax-2by+c=0
(-6)²+(-1)²-2a*(-6)-2b*(-1)+c=0
36+1+12a+2b+c=0
37+12a+2b+c=0


37-12a-2b+c=0
29+4a-10b+c=0
37+12a+2b+c=0

c=12a+2b-37
29+4a-10b+12a+2b-37=0
37+12a+2b+12a+2b-37=0

16a-8b-8=0
24a+4b=0

16a-8b-8=0
4b=-24a /:4

16a-8b-8=0
b=-6a

16a-8(-6a)-8=0
b=-6a

16a+48a-8=0
64a=8 /:64
a=8/64
a=1/8

b=-6a
b=-6*1/8
b=-6/8
b=-3/4

S=(a;b)
S=(1/8 ; -3/4)
17 4 17